Tourism in the least developed countries - Díaz Benavides, David; Pérez-Ducy, Ellen (Organización Mundial del Turismo, 2001)
The release of this publication is a joint effort of the World Tourism Organization and UNCTAD. It constitutes the outcome of the High-Level Meeting on Tourism and Development in LDCs, held in Maspalomas Gran Canaria, Spain, on 26-29 March 2001, as a preparatory event for the Third United Nations Conference on the Least Developed Countries. The wealth of information and the high-quality of the analysis in the papers submitted by invited experts and the monographs prepared by LDCs, together with the Canary Island Declaration and the report of the Meeting, provides a background and a point of reference of paramount importance. It will greatly facilitate carrying out forward-oriented actions designed to support the development of tourism as one of the driving forces in the refocusing of economic development strategies of LDCs.